Th17-mediated inflammation in asthma - Newcomb, Dawn C. (2013)
Asthma is a heterogeneous disease with many different phenotypes. Moderate and severe asthma phenotypes have been associated with increased neutrophils and increased Th17 cytokines, IL-17A, IL-17F, and IL-22, in the bronchoalveolar lavage fluid of patients. Th17 cytokines recruit neutrophils to the airway by increasing secretion of epithelial-derived neutrophilic chemokines. In addition, Th17 cytokines also induce mucous cell metaplasia and have pleotropic effects on airway smooth muscle resulting in airway narrowing. The role of Th17 cytokines in regulating Th2 cytokine expression and allergic airway inflammation remains unclear with conflicting reports. However, the role of Th17 cells in asthma will be answered in ongoing clinical trials with therapeutics targeting IL-17A and IL-17 receptor signaling.